2006
DOI: 10.5688/aj700101
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Competency-Based Assessment Process for Advanced Pharmacy Practice Experiences

Abstract: Objectives. To develop and implement a competency-based assessment process for the experiential component of a pharmacy education curriculum. Design. A consultative process was used in the development of new assessment forms and policies, and a survey regarding student and faculty satisfaction was conducted. Information received from the survey and from consultations with faculty preceptors resulted in revision of the forms in subsequent years. Assessment. Faculty and student perceptions of the assessment proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 8 publications
1
55
0
Order By: Relevance
“…These measures tend to be more qualitative or subjective than classroom grades and generally have been less accurate in predicting students' clinical success after graduation. [9][10][11][12] A detailed description of the various progress examinations in use has recently been presented. 13 Little has been done to identify factors that can predict clinical performance accurately, or to predict clinical success in a multidisciplinary patient-care setting.…”
Section: Introductionmentioning
confidence: 99%
“…These measures tend to be more qualitative or subjective than classroom grades and generally have been less accurate in predicting students' clinical success after graduation. [9][10][11][12] A detailed description of the various progress examinations in use has recently been presented. 13 Little has been done to identify factors that can predict clinical performance accurately, or to predict clinical success in a multidisciplinary patient-care setting.…”
Section: Introductionmentioning
confidence: 99%
“…4,9 Additionally, the American Society of Health System Pharmacists stated that "Pharmacists in organized health-care settings have a professional obligation to participate actively in and increase pharmacy-related and drug-related research efforts." 9 However, the opportunities for students to learn about basic research are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Key topics were defined according to reported findings and elective research rotation supportive rationale as previously reported. [4][5][6][7][8][9][10] Thirty-five topics were chosen and each topic was sequentially numbered in order to provide differentiation. The investigators were able to obtain 15 reflections from six of the 12 student pharmacists from the Experiential Education office of the college.…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
“…Its validity and reliability, however, have not been systematically evaluated. Several studies [6][7][8][9] have described the use of tools to evaluate student IPPE and APPE performance but, to our knowledge, no paper has been published that measures the performance of an instrument that used the CAPE 2013 competencies as core elements. This study was performed to explore the validity and reliability of PAST, which was developed to assess PharmD student rotation performance.…”
Section: Introductionmentioning
confidence: 99%